Matemáticas
alantapia2011
2

X (elevado a 2) + X = 6

+0
(2) Respuestas
dggchguesc

x²+x=6 x²+x-6=0 (x+3)(x-2)=0 x+3=0      x-2=0 x= -3        x=2 las dos soluciones son:  x= -3       x=2

kmiloo98

x² + x = 6 x² + x - 6 = 0 pero "x" lo podemos expresar como: "3x -2x" (nota que 3(-2) = -6 ) Entonces:  x² + 3x - 2x - 6 = 0  , factorizamos  x(x+3) - 2(x+3) = 0   (x-2)(x+3) = 0 para que la igualdad sea cierta:  x - 2 = 0 → x = 2                                            ó  x + 3 = 0 → x = -3 • Conjunto solución = { -3 , 2 } Saludos! Jeyson(Jmg)

Añadir respuesta